2021
DOI: 10.3389/fnagi.2021.742928
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effect on Visuomotor Adaptation: Mediated by Cognitive Decline

Abstract: The question of whether and how aging affects humans’ visuomotor adaptation remains controversial. This study investigates how the effect of aging on visuomotor adaptation is related to age-related cognitive declines. We compared the performance of 100 older people (age: 55–82 years) and 20 young adults (age: 18–27 years) on a visuomotor adaptation task and three cognition tasks. A decline in visuomotor adaptation of older people was well observed. However, this decline was not strongly correlated with chronol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Finally, we found no indications that sex affected visuomotor adaptation rates, although there was an overall smaller error for females than males across all study blocks. Several studies comparing younger and older adults propose that age-related reductions in sensorimotor adaptation may be linked to an age-related reduction in cognitive functions involved in such adaptation (e.g., Li et al, 2021; Vandevoorde & Orban de Xivry, 2019). For example, earlier work has demonstrated that spatial working memory-which could be used to apply an explicit aiming strategy-was positively associated with adaptability (Anguera et al, 2010(Anguera et al, , 2011Ruitenberg et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found no indications that sex affected visuomotor adaptation rates, although there was an overall smaller error for females than males across all study blocks. Several studies comparing younger and older adults propose that age-related reductions in sensorimotor adaptation may be linked to an age-related reduction in cognitive functions involved in such adaptation (e.g., Li et al, 2021; Vandevoorde & Orban de Xivry, 2019). For example, earlier work has demonstrated that spatial working memory-which could be used to apply an explicit aiming strategy-was positively associated with adaptability (Anguera et al, 2010(Anguera et al, , 2011Ruitenberg et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that age could affect visuomotor ability, but we did not find any correlation between age and the outcomes. The groups were homogenous and the participants were not older than 55 years because the age of >55 years has been associated with cognitive decline affecting visuomotor ability (Li et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The groups were homogenous and the participants were not older than 55 years because the age of >55 years has been associated with cognitive decline affecting visuomotor ability (Li et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To enhance EFs of older adults, the VR-based cognitive intervention was developed according to the extant literature suggesting the strong links between EFs, visuospatial WM (Brown et al, 2012;Miyake et al, 2001;Wang et al, 2018), and visuomotor adaptation (Li et al, 2021;Stirling et al, 2013) in an aging population. Furthermore, the VR content was developed to fulfill six psychological processes (i.e., sensory memory, encoding, planning, movement control, active manipulation, and adaptation).…”
Section: Vr-based Cognitive Interventionmentioning
confidence: 99%